Morphological characterization of a highly-dynamic fluvial landscape: The River Baker (Chilean Patagonia). (October 2018) - Ulloa, H.; Mazzorana, B.; Batalla, R.J.; Jullian, C.; Iribarren-Anacona, P.; Barrientos, G.; Reid, B.; Oyarzun, C.; Schaefer, M.; Iroumé, A.
Abstract: Characterizing river corridors from a hydro-morphological standpoint is a fundamental requisite for the analysis of their past evolution and for the plausible prediction of how rivers may adjust to changing climatic conditions and to increasing human impacts. The River Baker (Chilean Patagonia) is a highly dynamic fluvial system with relatively limited human intervention, which flows throughout a mountainous landscape following a narrow floodplain which widens towards the Pacific Ocean. Here, we characterize its current morphology as a basis for understanding its geomorphic dynamics, using satellite images as data source and following a hierarchical classification procedure. The Baker was divided into 9 segments and 34 reaches based on channel confinement and geometry. The geomorphic classification resulted in several confined (41%) and semiconfined (53%) reaches, whereas only 6% of them were classified as unconfined. Most of the confined reaches were single thread and the majority of the semiconfined ones were sinuous. Braided reaches were identified in all confinement categories and represent 30% of the reaches. We identified and characterized 246 islands and 393 fluvial bars and delimited 170 wetlands. Finally, we could statistically relate the island density to the braiding index, active channel width and sinuosity index, whereas the presence of bars is influenced by the active channel width, and degree of braiding and sinuosity. This characterization represents a starting point in the geomorphological analysis of the river and serves as a basis to plan future investigation efforts aiming at unravelling the morpho-dynamics of this unexplored large austral fluvial system. Highlights: Active channel width increases exponentially in the downstream direction. The majority of river segments in the Baker are confined and semiconfined. Presence of bars depends on active channel width, braiding and sinuosity. Tributaries do not significantly alter geomorphic indicators of the mainsteam Baker. Sediment excess in the valley is reflected in the convex shape of river's profile.